DICROMATOMETRIA EM MICROESCALA: MOTIVAÇÃO PARA DIMINUIR OS IMPACTOS AMBIENTAIS NO ENSINO DA QUÍMICA ANALÍTICA - Gabriel N. F. Netto; Flávia F. de C. Marques; Rafaella R. A. Peixoto; Christiane B. Duyck (Química Nova)
The introduction of the concepts of Green Analytical Chemistry in the teaching of Chemistry has been growing, in view of the formation of students more attentive to sustainable development. However, many experimental classes still employ reagents of high toxicity, which generate class I residues, as is the case of dichrometry, a titulometric method. Using the determination of iron in a dietary supplement and in a steel sponge as motivating examples, this paper presents microtitration as a greener alternative for classroom use. The method is compared to the classical approach, highlighting differences in chemical exposure and waste volume, emphasizing the environmental benefits of microtitration. The experiment allowed students to develop critical thinking about traditional methods and became familiar with the manipulation of microvolumes and microscale reasoning. Their evaluations of the proposed practice were recorded and discussed, for a possible replacement of the classical method.